THE INFLUENCE OF LEADERSHIP, WORKLOAD, AND ORGANIZATONAL CITIZENSHIP BEHAVIOR ON EMPLOYEE PERFORMANCE ON PT. BANK MANDIRI SEMARANG BRANCH - Gabriella Lena Talentania Rering; Kis Indriyaningrum (Jurnal Ekonomi, 2022)
This study aims to analyze the effect of "Leadership, Compensation, and Organizational Citizenship Behavior on employee performance at PT Bank Mandiri Semarang. The population in this study were 100 employees and everything becomes samples research. Analysis techniques include: model analysis, hypothesis testing. The data collection process of PT Bank Mandiri Semarang employees using research instruments in the form of questionnaires distributed to the entire sample. Based on the results of data analysis that has been carried out, it can be concluded that: leadership has a positive and significant effect on employee performance, workload has a positive and significant effect on employee performance, and organizational citizenship behavior has a positive and significant effect on employee performance.